2015
DOI: 10.12965/jer.150203
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of deep and superficial abdominal muscle activity between experienced Pilates and resistance exercise instructors and controls during stabilization exercise

Abstract: Pilates and resistance exercises are used for lumbar stabilization training. However, it is unclear which exercise is more effective for lumbar stabilization. In our study, we aimed to compare surface muscle activity and deep muscle thickness during relaxation and spinal stabilization exercise in experienced Pilates and resistance exercise instructors. This study is a retrospective case control study set in the Exercise Prescription Laboratory and Sports Medicine Center. The participants included Pilates instr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 25 publications
0
19
0
1
Order By: Relevance
“…The participant is asked to breathe in and tuck the chin in toward the body. Then, the participant is asked to breathe out while rolling up and lifting the upper body [72].…”
Section: Roll-upmentioning
confidence: 99%
See 2 more Smart Citations
“…The participant is asked to breathe in and tuck the chin in toward the body. Then, the participant is asked to breathe out while rolling up and lifting the upper body [72].…”
Section: Roll-upmentioning
confidence: 99%
“…The supporting leg keeps knee flexion and one foot on the floor. This exercise may vary depending on specific protocols (e.g., foam roll or balance cushion as foot support) [39,67,72].…”
Section: Straight One-leg Holdmentioning
confidence: 99%
See 1 more Smart Citation
“…Hundred is a typical abdominal exercise among Pilates motions, and it is reported that Hundred affects the thickness increase of muscle TrA and IO and EO muscles as well as increase in muscle activity of EO muscle, IO muscle [24][25][26]. The study of muscle activity through EMG by Lee & Jeong [25] also reported that the muscle activity of RA muscle and EO muscle increased during Pilates Hundred motion.…”
Section: Introductionmentioning
confidence: 99%
“…Pilates exercises on deep abdominal muscle thickness increased significantly higher compared to resistance exercises [7] We need to investigate short time (8 weeks) effect of Pilates exercise on the important abdominal muscle rectus abdominis. In this way we have an idea of cost and time effect of Pilates exercise to plan new study.…”
Section: Introductionmentioning
confidence: 99%